2015
DOI: 10.1007/s10856-015-5625-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion on biomedical surfaces covered by yttria stabilized zirconia

Abstract: The aim of this study was to compare the bacterial adhesion of Staphylococcus spp. on Ti-6Al-4V with respect to Ti-6Al-V modified alloys with a set of Cubic yttria stabilized zirconia (YSZ) and Ag-YSZ nanocomposite films. Silver is well known to have a natural biocidal character and its presence in the surface predicted to enhance the antimicrobial properties of biomedical surfaces. Microbial adhesion tests were performed using collection strains and twelve clinical strains of Staphylococcus aureus and Staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…6 The adherence and colonization of either bacterial cells or tissue cells on biomaterials have often been addressed as separate issues. [7][8][9][10] On the one hand, the outcome of the race for the surface between bacteria and tissue cells appears to be dependent on the initial number of bacteria present prior to cell seeding, as suggested by the fact that both the number of host cells and spread area per host cell decreases with increasing density of adhering bacteria. 11,12 However, the influence of the critical initial event of Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
“…6 The adherence and colonization of either bacterial cells or tissue cells on biomaterials have often been addressed as separate issues. [7][8][9][10] On the one hand, the outcome of the race for the surface between bacteria and tissue cells appears to be dependent on the initial number of bacteria present prior to cell seeding, as suggested by the fact that both the number of host cells and spread area per host cell decreases with increasing density of adhering bacteria. 11,12 However, the influence of the critical initial event of Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
“…ZrO 2 and particularly YSZ nanoparticles present high ionic conductivity, mechanical strength, chemical inertness, high melting point, low thermal conductivity [50] as well as biocompatibility [51], characteristics that make zirconia nanoparticles attractive for a wide range of applications. Yttria-stabilized zirconia nanoparticles offer multiple advantages compared to pure ZrO 2 in terms of high mechanical properties, antibacterial properties and low thermal conductivity that make them attractive candidates for fillers in dental cement and composite materials [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, processes aimed at nanotexturing ZrO 2 revealed a reduction in bacterial adhesion [ 107 ] ( Table 2 ). In addition, authors reported [ 108 ] the development of a surface based on Ti-coated alloy with a combination of cubic stabilized zirconia and silver films, significantly reducing the adhesion of bacteria such as Staphylococcus aureus and Staphylococcus epidermidis which are responsible for peri-implant pathology.…”
Section: Biological Responsesmentioning
confidence: 99%